CCAFS Knowledge by the Numbers 2017 - Abreu, David; Epp, Marissa van; García, Ángela (2019)
This newsletter is a snapshot and analysis of CCAFS knowledge and data sharing achievements (data, publications and so on) for 2016. We hope this will help encourage you to embrace Open Access and FAIR principles (Findable, Accessible, Interoperable, Re-usable) compliance as much as possible, and that you will discover new and interesting publications and data for use in your work. We want your feedback, so we can better tailor this bulletin to your interests so please do get in touch.